Growth rate and carbon storage capacity of mangroves along the Tambakrejo Coastal Zone - Agustina, Muhammad Agung Triyudha; Rahmi, Muthiah Aini; Aristia, Alma Cantika; Indahyati, Fahriza Dwi; Robani, Miftachur; Ichsan, Amiul; Syadzali, Chashif; Nurhayati, Nurhayati; Mutiara, Sarah (Foresty Faculty of Hasanuddin University, 2024)
The existence of mangroves is essential as a mitigation agent of the impacts of climate change. Mangroves serve as abrasion protection and a carbon storage agent, reducing greenhouse gas emissions. This study aimed to examine growth rate and carbon storage of mangroves as a determination of a rehabilitation potential for abrasion-exposed degraded mangroves. This study used a quantitative approach. Data was collected in November 2021 at the Tambakrejo coast, located in the north coast of Semarang. The results showed that the highest growth rate occurred in the 5–6-year period with the diameter of 0.11 cm (about 0.04 inch)/month and in the 4–5-year period with the height of 3.54 cm (about 1.39 inch)/month. The regression analysis showed moderate level of relationship between diameter and height values. This was used to determine both height and diameter values. Among different tree age classes, the age class of 72 showed the highest storage capacity, reaching 45.6 kg CO2eq, with average annual addition of 7.5 kgCO2eq/year. This indicates biomass addition is positively related to the storage capacity. Thus, anything that can alter the mangrove tree biomass will affect its carbon storage capacity.